(untitled) (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2024)
The global dialogue on balancing economic development, human rights protection, and environmental preservation necessitates contributions from religions with their universal values. This article elucidates the role of Islamic law in maintaining the balance between human rights and environmental sustainability through political practices and policies in Indonesia. This study employs a descriptive-analytical method with a qualitative approach. Data collection is conducted through literature review and analyzed using content analysis. The findings of this research indicate that the concepts of maslahah (public interest) and maqasid al-shariah (objectives of Islamic law) have played a crucial role in providing fundamental principles for various sustainable policies. Islamic legal politics, through the principles of tawazun (balance) and avoiding harm, have fostered a restraint from excessive exploitation of natural resources to maintain ecological balance. The principles of maslahah and maqasid al-shariah offer a strong ethical and moral foundation for sustainable policies and support global efforts towards environmental sustainability and social welfare.